Construct validity and internal consistency in the leisure practices scale (EPL) for adults Validade de construto e consistência interna da Escala de Práticas no Lazer (EPL) para adultos - Andrade R.D.* (2018)
© 2018, Associacao Brasileira de Pos - Graduacao em Saude Coletiva. All Rights Reserved.This study proposes and analyzes the construct validity and internal consistency of the Leisure Practices Scale (EPL). This survey seeks to identify the preferences and involvement in in different leisure practices in adults. The instrument was formed based on the cultural leisure content (artistic, manual, physical, sports, intellectual, social, tourist, virtual and contemplation/leisure). The validation process was conducted with: a) content analysis by leisure experts, who evaluated the instrument for clarity of language and practical relevance, which allowed the calculation of the content validity coefficient (CVC); b) reproducibility test-retest with 51 subjects to calculate the temporal variation coefficient; c) internal consistency analysis with 885 participants. The evaluation presented appropriate coefficients, both with respect to language clarity (CVCt = 0.883) and practical relevance (CVCt = 0.879). The reproducibility coefficients were moderate to excellent. The scale showed adequate internal consistency (0.72). The EPL has psychometric quality and acceptable values in its structure, and can be used to investigate adult involvement in leisure activities.